Mudanças institucionais e gestão pública: sobre a reforma gerencial de 1995 - Miranda, Daniel Estevão Ramos de (Universidade Federal de São Carlos, 2010)
This research has as object the Brazilian managerial reform of 1995. Situating it in the context of transformations through which Brazil was passing since end of seventies, context that was marked by the democratic transition, aims to contribute to a greater understanding of that experience of administrative reform. It is propose here that the ways and proportions that the managerial reform has assumed were strongly influenced (i) by the form as the redemocratization process and the eighties crises ended, that means, by the hegemonic affirmation of a reforms platform by the election of Fernando Henrique Cardoso FHC to the Presidency of Republic and (ii) by the role of Bresser- Pereira, Administration Minister of period, and its team with the aims of to elevate the legitimation degree of its proposals, and, consequently, of to get more supports and resources. The main conclusion is that MARE (Administrative and State Reform Ministry) became one the greater gravitation centers of the debates involving the historical signification and purposes of FHC government, despite it do not be among the mains responsible actors by the concretization of the big reforms conceived for the restructuration of Brazilian public sector.
Keywords: Democracia; Brasil - transição política; Reforma do estado; Governo Fernando Henrique Cardoso; Transição democrática; Reforma administrativa; Governo FHC; Democratic transition; Administrative reform; FHC government; CIENCIAS HUMANAS::CIENCIA POLITICA